Effect of glycerol on flow ability of swine diets - C N Groesbeck; Leland J McKinney; Michael D Tokach; Jim L Nelssen; Joel M DeRouchey; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2007)
We conducted two experiments to determine the effect of added glycerol or a 50:50 soy oil/glycerol blend on the flow ability characteristics of ground corn or ground corn and 15 or 30% spray-dried whey. Experiments were conducted using corn ground by either a full circle, tear drop hammer mill or a three-high roller mill at the Kansas State University Grain Science Feed Mill. Flow ability was determined by measuring angle of repose. In Exp. 1 we evaluated the effects of added soy oil, glycerol, or a 50:50 soy oil/glycerol blend on the flow ability of ground corn. Samples were ground through a roller mill (RM) or hammermill (HM). Particle size mean and standard deviations of the ground corn were 645 microns and 1.97 for the roller mill and 674 microns and 2.31 for the hammer mill. Soy oil, glycerol, or a 50:50 blend of soy oil/glycerol was added to the ground corn at 0, 2, 4, 6, or 8% for a total of 30 samples (1 RM sample, 1 HM sample, 3 liquid sources, and 5 levels of added liquid). In Exp. 2, we evalu-ated the effects of added soy oil, glycerol, or a 50:50 soy oil/glycerol blend on the flow ability of 85:15 or 70:30 blend of HM ground corn and spray-dried whey. Soy oil, glycerol, or a 50:50 blend of soy oil/glycerol was added to the ground corn and spray-dried whey-based diets at 0, 4, or 8% for a total of 18 samples (1 HM sample, 2 levels of added whey, 3 liquid sources, and 3 levels of added liquid). Angle of repose was then measured, and replicated 4 times on each sample. In Exp. 1 there was a three way interaction (P<0.05) between mill type, liquid source, and percent liquid added. Roller mill ground grain had decreased angle of repose (better flow ability) compared to HM ground grain. The addition of soy oil increased angle of repose, decreasing flow ability. The addition of glycerol or a 50:50 soy oil/glycerol blend decreased angle of repose, improving flow ability with HM ground corn. Addition of glycerol did not influence flow ability when added to RM corn ground. In Exp. 2 there was a three way interaction (P<0.05) between spray-dried whey level, added liquid source, and percent of liquid added. The addition of glycerol or the 50:50 soy oil/glycerol blend decreased angle of repose, improving flow ability. The addition of glycerol decreased angle of repose greater in the 15% spray-dried whey sample compared to the 30% spray-dried whey sample. The addition of soy oil increased angle of repose regardless of spray-dried whey concentration. These data suggest that the addition of glycerol to a meal diet containing HM ground corn will improve flow ability.; Swine Day, 2007, Kansas State University, Manhattan, KS, 2007
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-121-S; Swine day; 2007; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 985; Swine; Feed manufacturing; Glycerol; Flow ability